Mechanical effects of surgical variations in the femoral neck system on Pauwels type III femoral neck fracture - Jung, C. H.; Cha, Y.; Yoon, H. S.; Park, C. H.; Yoo, J. I.; Kim, J. T.; Jeon, Y. (Bone and Joint Research, 2022)
Aims In this study, we aimed to explore surgical variations in the Femoral Neck System (FNS) used for stable fixation of Pauwels type III femoral neck fractures. Methods Finite element models were established with surgical variations in the distance between the implant tip and subchondral bone, the gap between the plate and lateral femoral cortex, and inferior implant positioning. The models were subjected to physiological load. Results Under a load of single-leg stance, Pauwels type III femoral neck fractures fixed with 10 mm shorter bolts revealed a 7% increase of the interfragmentary gap. The interfragmentary sliding, compressive, and shear stress remained similar to models with bolt tips positioned close to the subchondral bone. Inferior positioning of FNS provided a similar interfragmentary distance, but with 6% increase of the interfragmentary sliding distance compared to central positioning of bolts. Inferior positioning resulted in a one-third increase in interfragmentary compressive and shear stress. A 5 mm gap placed between the diaphysis and plate provided stability comparable to standard fixation, with a 7% decrease of interfragmentary gap and sliding distance, but similar compressive and shear stress. Conclusion Finite element analysis with FNS on Pauwels type III femoral neck fractures revealed that placement of the bolt tip close to subchondral bone provides increased stability. Inferior positioning of FNS bolt increased interfragmentary sliding distance, compressive, and shear stress. The comparable stability of the fixation model with the standard model suggests that a 5 mm gap placed between the plate and diaphysis could viably adjust the depth of the bolt.
Keywords: Femoral neck fracture; Femoral neck system; Finite element analysis